Ferrocene-integrated conjugated microporous polymer nanosheets: Active and regenerative catalysts for photomediated controlled radical polymerization. (March 2020) - He, Jianqiao; Wang, Yan; Yuan, Jiayin; Liu, Cheng; Pan, Chunyue; Weng, Zhihuan; Tang, Xiang; Liu, Younian; Yu, Guipeng
Graphical abstract: Ferrocene-functionalized microporous nanosheets with high specific surface areas were constructed through a facile one-pot Schiff-base condensation reaction. The nanosheet catalyst succeed in initiating polymerizations of methyl methacrylate, methacrylate and styrene, producing polymers with controlled molecular weight and relatively low polydispersity index, and was recycled 10 times without sacrifice of its catalytic performance. Highlights: Ferrocene-based microporous nanosheets with high chemical stability were constructed by Schiff-base reaction. It succeeds in initiating polymerizations of 3 common vinyl monomers, producing polymers with relatively low dispersity. It shows good recyclability for at least 10 cycles without sacrifice of its catalytic performance. Abstract: The challenge of light-driven controlled radical polymerization through non-noble metal catalyst remains the most significant issue. Ferrocene-bearing microporous aromatic polymer nanosheets (termed "FeMAP-11") that feature high chemical stability were reported here to synergistically combine the advantageous properties of the redox-active ferrocene units and the conjugated microporous polymers (CMPs), and to be able to serve as photocatalyst for activators regenerated by electron transfer atom transfer radical polymerization (AGET-ATRP). It succeeded in initiating polymerizations of 3 common vinyl monomers, i.e. methyl methacrylate (MMA), methacrylate (MA) and styrene (St), and produced polymers with controlled molecular weight and relatively low molecular weight dispersity (˜1.3). Beneﬁting from steric hindrance through ketone-amine chemistry, the microporous catalyst with tolerance to acidic and basic media was found stable under the AGET-ATRP conditions. It showed negligible metal leaching and good recyclability for at least 10 cycles without sacrifice of its catalytic performance. Our tests proved that FeMAP-11 exceeded the state-of-the-art ATRP photocatalysts such as UiO-66-NH2, titanium MOF-901 and the commercial P-25 Titania, demonstrating promising potential in catalysis in view of green chemistry.